2014
DOI: 10.3892/ol.2014.1959
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation supernatants of Lactobacillus delbrueckii inhibit growth of human colon cancer cells and induce apoptosis through a caspase 3-dependent pathway

Abstract: Probiotic bacteria are known to exert a wide range of beneficial effects on their animal hosts. Therefore, the present study explored the effect of the supernatants obtained from Lactobacillus delbrueckii fermentation (LBF) on colon cancer. The results indicated that the proliferation of LBF solution-treated colon cancer SW620 cells was arrested and accumulated in the G1 phase in a concentration-dependent manner. The LBF solution efficiently induced apoptosis through the intrinsic caspase 3-depedent pathway, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 16 publications
(18 reference statements)
2
28
0
Order By: Relevance
“…Moreover, the relative abundance of the Lactobacillales order was decreased in colitic Il10 −/− and in AOM/ Il10 −/− mice, and in both cases, dietary curcumin restored this order to control levels. Lactobacillus strains have been used successfully in the CRC prevention in animal models 5154 , have been shown to exhibit significant antigenotoxicity 55 , and the Lactobacillus genus was shown to be associated with cell cycle arrest and induction of apoptosis in colon cancer cell lines 5657 . Although the results of systematic and well-controlled clinical studies in CRC prevention are not yet available, published reports suggest cautious optimism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the relative abundance of the Lactobacillales order was decreased in colitic Il10 −/− and in AOM/ Il10 −/− mice, and in both cases, dietary curcumin restored this order to control levels. Lactobacillus strains have been used successfully in the CRC prevention in animal models 5154 , have been shown to exhibit significant antigenotoxicity 55 , and the Lactobacillus genus was shown to be associated with cell cycle arrest and induction of apoptosis in colon cancer cell lines 5657 . Although the results of systematic and well-controlled clinical studies in CRC prevention are not yet available, published reports suggest cautious optimism.…”
Section: Discussionmentioning
confidence: 99%
“…40,62 Analysis with the focus on the most abundant KEGG orthologs, which were affected by curcumin-supplementation in AOM/ Il10 −/− mice showed reduced abundance of functions involved in transport, transcription factors, bacterial chemotaxis and bacterial motility proteins. 56, 57, 61, 6367 Curcumin has been observed to inhibit bacterial motility and cytotoxicity of Vibrio vulnificus 68 , to arrest Helicobacter pylori growth during infections 69 , as well as inhibit biofilm formation in Pseudomonas aeruginosa 70 . This suggests that the protective effect of 0.5% curcumin diet shifts the microbial composition to be more stationary, which may contribute to a decrease in microbial invasiveness and a decrease in overall disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…40,62 Analysis with the focus on the most abundant KEGG orthologs, which were affected by curcuminsupplementation in AOM/Il10 −/− mice showed reduced abundance of functions involved in transport, transcription factors, bacterial chemotaxis and bacterial motility proteins. 56,57,61,[63][64][65][66][67] Curcumin has been observed to inhibit bacterial motility and cytotoxicity of Vibrio vulnificus 68 , to arrest Helicobacter pylori growth during infections 69 , as well as inhibit biofilm formation in Pseudomonas aeruginosa 70 . This suggests that the protective effect of 0.5% curcumin diet shifts the microbial composition to be more stationary, which may contribute to a decrease in microbial invasiveness and a decrease in overall disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was highlighted that the upregulation of early apoptosis gene markers cfos and cjun constitutes the major mechanism involved in cytotoxicity of cell free supernatants of probiotic cultures toward colon cancer HT-29 and HCT116 cells (Shyu et al, 2014). Further, it has been documented that supernatants of Lactobacillus delbrueckii were able to induce apoptosis through intrinsic pathway and downregulation of Bcl-2 along with arrest of colon cancer cells in G1 phase (Wan et al, 2014). Conditioned medium of Bacillus polyfermenticus (BPCM) effectively suppressed the growth of colon cancer cells (HT-29, DLD-1, and Caco-2) and reduced their colony formation on soft agar due to decreased cyclin D1, ErbB2, and ErbB3 [epidermal growth factor receptors (EGFRs)] expression and inhibited tumor growth in mice because of heat stable bacterial proteins (Ma et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Butyrate hindered the activity of MMPs due to activation of tissue inhibitor matrix metalloproteinase (TIM) 1- and 2 (Adom and Nie, 2013). Another study observed that supernatants of Lactobacillus delbrueckii ameliorated cell invasion in colon cancer cells by decreasing MMP-9 activity (Wan et al, 2014). Further, it was revealed that fermented products of synbiotic (inulin and oligofructose with LGG and/or Bifidobacterium lactis BB12) inhibited cell invasion both in vitro and in experimentally induced colon carcinogenesis in rats (Pool-Zobel, 2005; Pool-Zobel and Sauer, 2007).…”
Section: Introductionmentioning
confidence: 99%